Foreign trade growth and economic development in China retrospective and future prospects - Jin, Zhesong (Enrich series on China's economic reform, 2011)
This series covers a wide range of economic issues related to contemporary China. Tracking the future trend in China's economic development, this account discusses monetary policy, fiscal policy, the growth of regional economies, and industrial and banking developments.